PERAN ILO MELALUI PROYEK EAST DALAM UPAYA PENCEGAHAN PEKERJA ANAK DI INDONESIA - Rita Melani, Ni Made; Wiranata, S.IP., M.A, I Made Anom; Resen, S.IP., M.A, Putu Titah Kawitri (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2014)
ABSTRACT Child labour is one of the human rights violation issue that is faced by the international community today. Indonesia is a country that still has to face the problem of child labour. ILO as an international organization initiates an international program for the elimination of child labour and participates in assisting government’s efforts in tackling child labour in Indonesia. One of ILO’s efforts is done through the EAST Project. This study aims to describe the role of ILO in effort to prevent and to eliminate child labor in Indonesia through Education and Skills Training Program for Youth in Indonesia (EAST). This study will be assessed by using the theories and concepts of International Organizations, Child Labour, and Development Intervention, with the locus from 2006 to 2011 which is the period for ILO - EAST Project held in Indonesia. Keywords : ILO, Child Labour, Indonesia, EAST